2002
DOI: 10.1093/hmg/11.25.3237
|View full text |Cite
|
Sign up to set email alerts
|

Loss of holocytochrome c-type synthetase causes the male lethality of X-linked dominant micro-phthalmia with linear skin defects (MLS) syndrome

Abstract: Girls with MLS syndrome have microphthalmia with linear skin defects of face and neck, sclerocornea, corpus callosum agenesis and other brain anomalies. This X-linked dominant, male-lethal condition is associated with heterozygous deletions of a critical region in Xp22.31, from the 5' untranslated region of MID1 at the telomeric boundary to the ARHGAP6 gene at the centromeric boundary. HCCS, encoding human holocytochrome c-type synthetase, is the only gene located entirely inside the critical region. Because s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…For example, chromosomal mutations in the gene encoding HCCS can lead to a condition called "microphthalmia with linear skin defects syndrome" (25,26). Additionally, a role for HCCS in apoptosis (separate from that of cytochrome c) has been described in injured motor neurons (27).…”
mentioning
confidence: 99%
“…For example, chromosomal mutations in the gene encoding HCCS can lead to a condition called "microphthalmia with linear skin defects syndrome" (25,26). Additionally, a role for HCCS in apoptosis (separate from that of cytochrome c) has been described in injured motor neurons (27).…”
mentioning
confidence: 99%
“…As expected for a gene subject to XCI, the phenotype of these mice is variable: from apparently unaffected and growth delayed to severely runted, with smaller eyes and brain in one animal. We also reported that when the mice are crossed with mice that are transgenic for a human BAC expressing the HCCS gene from its endogenous genomic locus, hemizygous, homozygous and heterozygous deleted animals survive intact (Prakash et al, 2002). These findings prove that loss of function of HCCS causes male lethality and suggest that heterozygous loss of function of this gene causes most phenotypic features of human MLS syndrome in females.…”
Section: Mouse Model For Mls Syndromementioning
confidence: 62%
“…No male mice hemizygous for this deletion are born, while heterozygous deleted females only rarely survive to adulthood. We previously reported one such surviving animal (Prakash et al, 2002). Since then, extensive breeding has resulted in an additional three heterozygous deleted females, suggesting that, similar to the human disorder, liveborn affected females are rare.…”
Section: Mouse Model For Mls Syndromementioning
confidence: 99%
“…Chromosome engineering and transgenesis (Prakash et al, 2002) Duchenne Muscular Dystrophy (DMD) del(X)(p21.2p21.2) 310200 DMD Mdx mouse model (Sicinski et al, 1989); inducible transgenesis (Ahmad et al, 2000); transgenesis (Cox et al, 1993;Phelps et al, 1995;Rafael et al, 1996;Wells et al, 1995) Hyperglycerolemia (GKD) del(X)(p21p21) 307030 GK Gyk targeted mutagenesis (Huq et al, 1997) usually occurs in most patients because of the molecular mechanism that results in fixed breakpoints reflecting genome architecture. In cases wherein it was not possible to identify patients harboring varying-sized deletions/duplications, or single gene mutations were not found, or a translocation disrupting a particular gene in the critical region was not available, murine models have proven to be extremely valuable for elucidating the predominant gene(s) responsible for the phenotype.…”
Section: Pmp22mentioning
confidence: 99%